Illustrated Guide to Nature : From Your Back Door to the Great Outdoors : Wildflowers, Trees & Shrubs, Rocks & Minerals, Weather, Night Sky (Washington, D.C. National Geographic Society, 2014)
This comprehensive nature field guide introduces you to constellations and weather, rocks and minerals, plants and wildflowers, and trees and shrubs.
Bursting with beautiful images and completely authoritative text, this comprehensive nature field guide will help families, amateur adventurers, and empty nesters enjoy and understand nature--from wilderness camping to their own backyard. This nature guide introduces you to constellations and weather, rocks and minerals, plants and wildflowers, and trees and shrubs. All of the most common varieties in each natural category in North are identified and explained, from quartz and granite to dandelions and oak trees. Learn to read the clouds--and understand why one shape predicts rain and another sunshine. Point out constellations in the night sky and recognize planets visible to the naked eye. Each chapter identifies 160 species or phenomena by giving key information for each plus a readable paragraph accompanied by photos and original art that help you sharpen your eyes and knowledge. Five field guides in one, representing a total of 800 of North America's most common wildflowers, trees, rocks and minerals, constellations, and weather patterns. Generously illustrated and logically organized with pointers, pictures, and identification tips, this is the ultimate field guide, an essential family reference and an excellent starting point for anyone eager to learn more about the natural world.
Include Color Illustrations and Index.
From Your Back Door to the Great Outdoors : Wildflowers, Trees & Shrubs, Rocks & Minerals, Weather, Night Sky.
Keywords: Natural history -- North America -- Plants -- Rocks--Identification -- Climatology